From classical approaches to new developments in genetic engineering of live attenuated vaccine against cutaneous leishmaniasis: potential and immunization - Rooholamini, Zahra; Dianat-Moghadam, Hassan; Esmaeilifallah, Mahsa; Khanahmad, Hossein (Frontiers in Public Health, 2024)
Despite the development of a vaccine against cutaneous leishmaniasis in preclinical and clinical studies, we still do not have a safe and effective vaccine for human use. Given this situation, the search for a new prophylactic alternative to control leishmaniasis should be a global priority. A first-generation vaccine strategy—leishmanization, in which live Leishmania major parasites are inoculated into the skin to protect against reinfection, is taking advantage of this situation. Live attenuated Leishmania vaccine candidates are promising alternatives due to their robust protective immune responses. Importantly, they do not cause disease and could provide long-term protection following challenges with a virulent strain. In addition to physical and chemical methods, genetic tools, including the Cre-loxP system, have enabled the selection of safer null mutant live attenuated Leishmania parasites obtained by gene disruption. This was followed by the discovery and introduction of CRISPR/Cas-based gene editing tools, which can be easily and precisely used to modify genes. Here, we briefly review the immunopathology of L. major parasites and then present the classical methods and their limitations for the production of live attenuated vaccines. We then discuss the potential of current genetic engineering tools to generate live attenuated vaccine strains by targeting key genes involved in L. major pathogenesis and then discuss their discovery and implications for immune responses to control leishmaniasis.